Run for the hills : a novel - Wilson, Kevin, 1978- (Ecco, an imprint of HarperCollins Publishers, 2025)
"An unexpected road trip across America brings a family together in this raucous and moving new novel from the bestselling author of Nothing to See Here. Ever since her dad left them twenty years ago, it's just been Madeline Hill and her mom on their farm in Coalfield, Tennessee. While she sometimes admits it's a bit lonely, and a less exciting a life than she imagined for herself, it's mostly ok. Mostly. Then one day, Reuben Hill pulls up in a PT Cruiser and informs Madeline that he believes she's his half-sister. Reuben--left behind by their dad thirty years ago--has hired a detective to track down their father and a string of other half siblings. And he wants Mad to leave her home and join him for the craziest kind of road trip imaginable to find them all. As Mad and Rube--and eventually the others--share stories of their father, who behaved so differently in each life he created, they begin to question what he was looking for with each new incarnation. Who are they to each other? What kind of man will they find? And how will these new relationships change Mad's previously solitary life on the farm? Infused with deadpan wit, zany hijinks, and enormous heart, RUN FOR THE HILLS is a sibling story like none other--a novel about a family forged under the most unlikely circumstances, and united by hope in an unknown future"--